1964 em Sergipe : golpe civil-militar, protestantismo e a Cruzada Cristo Esperança Nossa - Santos, Ermerson Porto (2017)
The Civil-Military Coup, which deposed the president of the Republic João Goulart in Brazil in 1964, sought the support of institutions such as the Institute for Research and Social Studies / Brazilian Institute of Democratic Action (IPES-IBAD), Brazilian Bar Association (OAB), the National Conference of Brazilian Bishops (CNBB), evangelical churches, the mass media and broad sectors of the urban middle classes, with the objective of guaranteeing the ascendancy and permanence of the military in power and providing it with the minimum Of legitimacy. The city of Aracaju / SE hosted the Crusade Cristo Esperança Nossa, from September 20 to 27, 1964, an evangelical campaign interdenominacional, that is, promoted and directed by several Protestant churches of the State, but idealized by Presbyterians with the support of missionaries North Americans. This event was based on the preservation of moral and Christian values, in the midst of the establishment of the new political-institutional order in the country marked by authoritarianism. The crux of this crusade, based on the idea of "political field", "symbolic power" and habitus of Pierre Bourdieu (1996), is investigated to prove the hypothesis that this event contributed to the diffusion of the anti-communist ideology in Sergipe, Context of the Cold War. Through the press and oral testimony, some manifestations of popular religious and popular evangelical leaders have been able to find a position, often discreetly stated, in favor of the takeover of power in 1964 and in defense of Christian morality, although Christ Esperança Nossa Has not been, a priori, a political event in its essence. Actions such as these also fit into the political environment conducive to marches, such as the "Family March with God for Freedom", and other evangelization campaigns that represented the defense of conservative postulates typical of the society of that period.